The knockdown of the fusion oncogene KMT2A-AFF1 is associated with differential RNA splicing in human acute lymphoblastic leukemia cells - Grinev, Vasily V.; Heidenreich, Olaf (Experimental Biology and Biotechnology, 2018)
The fusion oncogene KMT2A-AFF1 is the outcome of translocation t (4; 11)(q21; q23). If this occurred at the level of early hematopoietic progenitors, this oncogene plays the role of one of the factors in the genesis of children acute lymphoblastic leukemia, the mechanism of which is not fully understood. In this work, it was shown that the KMT2A-AFF1 activity affects the state of transcriptome of leukemia cells. This effect is realized in two ways: through the differential expression of the target genes controlled by oncogene, and also through control of differential splicing. The presented results indicate the discovery of a new biological activity of oncogene KMT2A-AFF1, and it also opens new perspectives in study of t (4; 11)(q21; q23) positive leukemia.
Keywords: fusion oncogene KMT2A-AFF1; knockdown of expression; alternative RNA splicing; human leukemia cells